Sexual imagery and male-ego in Lawrence's “Tortoise Shout” and Ted Hughes' “Thought Fox” - Shaymaa Alsalihi; Tavgah Ghulam Saeed (University of Chitral Journal of Linguistics and Literature)
sexual imagery has been a significant phenomenon in modern literature as writers tend to enrich their writings with social taboos and erotic contents. This paper presents the poetry of D. H. Lawrence and Ted Hughes to show how those writers used sexual images to depict their male-ego, and their manhood. Concentrating on Freud`s psychosexual development, and the use of phallic symbols. Through examining Tortoise Shout by Lawrence, and Thought Fox by Hughes, the reader can notice the sexual images that resides behind their stanzas. Accordingly, this paper tries to discover the way both writers present those images.